(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Arif MF, Aristya GR, Subositi D, Sai AN, Kasiamdari RS. 2019. Short Communication: rbcL and matK chloroplast DNA composition of green chireta (Andrographis paniculata) from Indonesia. Biodiversitas 20: 3575-3583. Green chireta (Andrographis paniculata (Burm.f.) Wall. ex Nees.) is often used by the traditional community as a medicinal herb in Indonesia. However, nucleotide study of green chireta from Indonesia has never been done. The objectives of this study were to analyze the rbcL and matK chloroplast gene composition of green chireta from Indonesia and to analyze the relationship with other Andrographis species. The result proved that all the DNA composition of green chireta used in this study was similar to the A. paniculata from GenBank. The rbcL composition was similar to A. paniculata KF521878, A. paniculata JQ922118, and A. paniculata JQ230990 from GenBank while the matK composition was similar to A. paniculata LC461762. Total 501 bp of rbcL and 639 bp of matK can be aligned produced 167 and 213 amino acid from translation. The amino acid translation result showed no different expression from rbcL genes but there was one sample expressed different translations from the matK gene. The phylogenetic tree was reconstructed using the Neighbor-Joining method with 1000 bootstrap values and the Kimura 2-Parameter (K2P) model in the MEGA7 software. Both rbcL and matK genes grouped the samples into the same clade as A. paniculata from GenBank. No variation was detected from the rbcL gene but two haplotypes were detected from the matK gene. This composition and sequence data serve as a database for Andrographis species from Indonesia which can be used for various studies.